Genome-wide DNA hydroxymethylation changes are associated with neurodevelopmental genes in the developing human cerebellum - Wang, Tao (Oxford University Press, 2012)
5-Hydroxymethylcytosine (5-hmC) is a newly discovered modified form of cytosine that has been suspected to be an important epigenetic modification in neurodevelopment. While DNA methylation dynamics have already been implicated during neurodevelopment, little is known about hydroxymethylation in this process. Here, we report DNA hydroxymethylation dynamics during cerebellum development in the human brain. Overall, we find a positive correlation between 5-hmC levels and cerebellum development. Genome-wide profiling reveals that 5-hmC is highly enriched on specific gene regions including exons and especially the untranslated regions (UTRs), but it is depleted on introns and intergenic regions. Furthermore, we have identified fetus-specific and adult-specific differentially hydroxymethylated regions (DhMRs), most of which overlap with genes and CpG island shores. Surprisingly, during development, DhMRs are highly enriched in genes encoding mRNAs that can be regulated by fragile X mental retardation protein (FMRP), some of which are disrupted in autism, as well as in many known autism genes. Our results suggest that 5-hmC-mediated epigenetic regulation may broadly impact the development of the human brain, and its dysregulation could contribute to the molecular pathogenesis of neurodevelopmental disorders. Accession number: Sequencing data have been deposited to GEO with accession number GSE40539.